Evaluation of nutritional, anthropometric, and psychological outcomes in different metabolic and bariatric surgery techniques: a follow up study - Elham Hojaji; Zahra Veysi; Shadi Naderyan Fe’li; Neda Shalbaf; Moslem Arian; Cain C. T. Clark; Ahmad Reza Dorosty Motlagh (BMC Surgery)
Abstract Background Metabolic and bariatric surgery (MBS) is a suitable solution for the treatment of morbid obesity. Investigating an MBS method that has the best outcomes has always been the main concern of physicians. The current study aimed to compare nutritional, anthropometric, and psychological complications of individuals undergoing various MBS Techniques. Methods A total of 96 subjects, who had been already referred to the obesity clinic of Firoozgar Hospital, Tehran, Iran, for MBS, were selected for the study and were followed for one year after MBS. The dietary intakes of the participants were assessed using a Food Frequency Questionnaire (FFQ) on a daily, weekly, monthly, or yearly basis. The mental health of participants was done via the Symptom Checklist 90 Revised. Furthermore, the In-Body 720 bioelectrical impedance device was used to obtain the body composition of the participants at the beginning and the end of the study. Results The mean age of the participants was 39.5 ± 9.5 years. All anthropometric indices including weight, Body Mass Index (BMI), protein content, fat mass, and fat mass percentage decreased after Roux-en-Y gastric bypass (RYGB), one-anastomosis gastric bypass (OAGB), and sleeve gastrectomy (SG) surgeries (P < 0.05). After adjustments for confounders, no significant difference was observed in the magnitude of the changes in body composition between the three Techniques (p > 0.05). Energy and carbohydrate intake significantly decreased after surgeries in all three groups (p < 0.05), but comparing the methods no significant difference was revealed (p > 0.05). Furthermore, the results indicated that there was a significant relationship between the mental health of patients before and after surgeries (p < 0.05). Conclusion Overall, all three methods of surgery contributed to the improvement of the nutritional, anthropometric, and psychological complications. Further complementary studies are needed to determine the least complicated MBS method.